Nursing Work Environment as a Moderator of Patient Safety Competence and Incident Reporting - Erna Puspita Sari; Kuswantoro Rusca Putra; Yati Sri Hayati (Universitas Tribhuwana Tunggadewi, 2026)
Patient safety incident reporting is a critical component of healthcare quality improvement. However, underreporting remains a persistent challenge, influenced by both individual and organizational factors. This study aimed to examine the effect of patient safety competence and the nursing work environment on patient safety incident reporting and to analyze the moderating role of the nursing work environment in this relationship. A cross-sectional quantitative correlational study was conducted among nurses from three hospitals in Malang. The study population consisted of 370 nurses. A minimum sample size of 190 nurses was calculated using proportional quota sampling based on the proportion of eligible nurses in each participating hospital, with an anticipated 10% dropout rate. A Total of 224 eligible nurses completed an online questionnaire (Google Forms). Data were collected using three validated and reliable Indonesian versions of the instruments: PES-5, H-PEPSS and ROCAES. Data analysis was performed using Smart PLS 4 to examine direct effect and to test the moderating role of nursing work environment. Patient safety competence had a positive and significant effect on patient safety incident reporting (? = 0.182, p = 0.009). The nursing work environment also had a positive and significant direct effect on patient safety incident reporting (? = 0.309, p = 0.002). Furthermore, the nursing work environment functioned as a quasi-moderator, meaning that it had both a significant direct effect on patient safety incident reporting and a significant interaction effect with patient safety competence. These findings indicate that competence is more effectively translated into reporting behavior within supportive organizational environments. Both individual competence and organizational context are essential determinants of patient safety incident reporting. Healthcare institutions should integrate systematic competency development with efforts to create supportive, non-punitive work environments to enhance reporting practices and improve patient safety outcomes.